Pockets of promise: exploring innovation and complexity of remote ECEC service delivery in Australia - Adamson, Elizabeth; Skattebol, Jennifer (Frontiers in Education, 2023)
Introduction The existing funding architectures for early childhood education and care (ECEC) services in Australia are incompatible with the needs of remote and First Nations communities. The Australian system relies on a market-based model for ECEC – characterized by demand-led funding mechanisms where funding flows to users to choose what service to use. This model is not viable or sustainable in remote and First Nations communities. In this paper, we ask what we can learn from alternative models of ECEC that serve remote, largely Indigenous communities. Methods This research is based on interviews with 10 key stakeholders. Potential participants were identified using three selection criteria which established their expertise in relation to: advocacy and experience in delivering ECEC services in remote locations (evident in relevant parliamentary reviews and inquiries), in-depth knowledge about First Nations perspectives about ECEC models, and broader understandings of the ECEC system in Australia. Three themes were explored in the interviews: (1) funding context (including impact of recent changes to Budget Based Funding, and role of philanthropy in the ECEC sector); (2) Quality and regulatory context (including workforce challenges and cultural considerations); and (3) Future research (including research gaps, opportunities, and considerations). The study design and analysis of data was guided by policy studies frameworks that advocate for collaboration and coordination among researchers and stakeholders in order to address complex problems. Results Analysis of the interviews illuminated the complex structural and cultural elements shaping the design of, and access to, ECEC in remote communities. Stakeholders argued that the ECEC system should be universal in that it delivers services that meet the needs of young children and their families. This requires the development of a definition of ‘universality’ that enables communities to define their own ECEC needs and the types of services best suited to meet those needs. Stakeholders’ views about the importance of community-led design and delivery highlighted the need to align structural and cultural aspects of quality standards and workforce needs, and also to strengthen consultation with First Nations organisations to better understand community-specific solutions. Discussion The paper outlines the complexities and nuances of ECEC service delivery in remote communities. The findings are intended to foster discussion about current initiatives, challenges, and futures possibilities for ECEC in remote communities in Australia. These findings concur with other research that argues for community led service delivery and for stronger equity-based partnerships between First Nations and non-First Nations researchers and organizations.